2019
DOI: 10.3847/1538-4357/aafaf8
|View full text |Cite
|
Sign up to set email alerts
|

A Cancellation Nanoflare Model for Solar Chromospheric and Coronal Heating. II. 2D Theory and Simulations

Abstract: Recent observations at high spatial resolution have shown that magnetic flux cancellation occurs on the solar surface much more frequently than previously thought, and so this led Priest et al. (2018) to propose magnetic reconnection driven by photospheric flux cancellation as a mechanism for chromospheric and coronal heating. In particular, they estimated analytically the amount of energy released as heat and the height of the energy release during flux cancellation. In the present work, we take the next step… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 68 publications
3
59
0
Order By: Relevance
“…The WLF occurred synchronously to this flux cancellation process. The spatial-temporal correlation between flux cancellation and this WLF strongly suggests that this WLF is powered by magnetic reconnection in the lower solar atmosphere (e.g., Syntelis et al 2019). The two small sunspots disappeared about half an hour after the white-light enhancement, likely resulted from a reconfiguration of the magnetic field structure due to the reconnection.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The WLF occurred synchronously to this flux cancellation process. The spatial-temporal correlation between flux cancellation and this WLF strongly suggests that this WLF is powered by magnetic reconnection in the lower solar atmosphere (e.g., Syntelis et al 2019). The two small sunspots disappeared about half an hour after the white-light enhancement, likely resulted from a reconfiguration of the magnetic field structure due to the reconnection.…”
Section: Resultsmentioning
confidence: 97%
“…It is worth mentioning that one side of a U-shaped structure may reconnect with the surrounding magnetic field during flux emergence (e.g., Syntelis et al 2019;Chen et al 2019a). In principle this process could produce a flare.…”
Section: Resultsmentioning
confidence: 99%
“…It may be possible to generate temperatures as high as 25 kK through reconnection in the upper photosphere or lower chromosphere, as shown by Ni et al (2016Ni et al ( , 2018. Priest et al (2018) and Syntelis et al (2019) pointed out in a theoretical work that flux cancellation can cause simultaneous reconnection at different heights in the solar atmosphere. Hansteen et al (2017) found that both EBs and UV bursts were generated in a model where a flux sheet was injected some 2.5 Mm below the photosphere and allowed to emerge through the photosphere into an essentially magnetic field free corona.…”
Section: Introductionmentioning
confidence: 99%
“…In line with the scenario of footpoint heating, photospheric observations at the base of some active region coronal loops highlight the presence of mixed-polarity magnetic field patches that exhibit flux cancellation, a process through which energy can be supplied to heat the overlying corona (e.g., Chitta et al 2017aChitta et al , 2018. Two-dimensional (2D) and 3D magnetic reconnection models predict that such magnetic flux cancellation events at the solar surface, which would of course be associated with prior flux emergence, would trans-port energy to the loops in the upper solar atmosphere (Priest et al 2018;Syntelis et al 2019).…”
Section: Introductionmentioning
confidence: 99%